if ƒ:R−{0} -> R,  2ƒ(x) − 3ƒ(1⁄x) = x²  then ƒ(3)= ?

Answer Strategies and trick by Manish sir (it will help you to solve it by yourself)

2ƒ(x) − 3ƒ(1⁄x) = x²   (1)

so 2ƒ(1/x) − 3ƒ(x) = 1/x²  (2)

multiply (1) to 2 and (2) to 3, then add the two equations, you will get f(x) then calculate f(3)  

Submit Your Answer

submit your answer (you can use image and symbol from editor below "last 2 icon")

please login to submit your answer

Login Here

username / email :

password :

register | forget password